Postharvest Practices, Perceptions, and Knowledge of Mycotoxins among Groundnut Farmers in the Adamawa, Centre, and North Regions of Cameroon - Pierre Germain Ntsoli; Marie Ampères Boat Bedine; Cynthia Claire Baleba; Steve Freddy Tchatcho Ngalle; Idriss Djoko Kouam; Roland Wilfried Titti; Georges Marius Etame Kossi; Aoudou Yaouba (Scientifica)
In many parts of the world, including Cameroon, mycotoxin contamination of groundnuts remains a major constraint affecting their use as food. Understanding the contributing factors is an essential intervention to reduce contamination and people’s exposure to these harmful toxins. The aim of this research was to identify the factors associated with the knowledge, perceptions, and postharvest practices of groundnut farmers in three production basins in Cameroon. Data were collected through surveys and analyzed using descriptive methods and logistic regression models. The results show that groundnut farmers are little aware of the existence of mycotoxins (12%) and totally unaware of the existence of aflatoxins (100%). Only 7.1% of these farmers are aware of the effects of mycotoxins on consumer health. After evaluation, the large majority of farmers scored poor marks for knowledge (86%) and practice (98.7%) in the management of mould and mycotoxins in groundnuts. Knowledge of mycotoxins was positively associated with the level of education [OR = 3.42; (95%-IC: 1.00–16.00); p<0.05] and region [OR = 4.49; (95%-IC: 1.09–20.3); p<0.05]. Farmers’ good practices were linked to their production experience [OR = 6.06, (95% CI: 0.91-18.4), p=0.035]. The use of mouldy groundnut for feed was associated with age [OR = 3.34, (95% CI: 1.14–10.2), p=0.03], sex [OR = 0. 43, (IC-95%: 1.14–1.05), p=0.026], marital status [OR = 0.35, (IC-95%: 0.14–0.79), p=0.015], and production region [OR = 0.27, (IC-95%: 0.13–0.56)]. In conclusion, groundnut farmers had insufficient knowledge of mycotoxins, no knowledge of aflatoxins, and suboptimal handling and storage practices for this commodity. This contributes to increasing the risk of exposure for the population and requires mitigation measures, including awareness campaigns on mycotoxins, specifically aflatoxins, and capacity building for farmers in terms of storage and postharvest management of foodstuffs.